Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijms21176394
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing in Dentistry: Towards Application of Small Molecules in Dentin Repair

Abstract: One of the main goals of dentistry is the natural preservation of the tooth structure following damage. This is particularly implicated in deep dental cavities affecting dentin and pulp, where odontoblast survival is jeopardized. This activates pulp stem cells and differentiation of new odontoblast-like cells, accompanied by increased Wnt signaling. Our group has shown that delivery of small molecule inhibitors of GSK3 stimulates Wnt/β-catenin signaling in the tooth cavity with pulp exposure and results in eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Drug repositioning is intended to apply alternative uses for a drug that is developed by another investigator and besides its original medical purpose. It has advantages in nancial and time savings for drug development with the lower failure risk and reduced drug investigating time and costs [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…Drug repositioning is intended to apply alternative uses for a drug that is developed by another investigator and besides its original medical purpose. It has advantages in nancial and time savings for drug development with the lower failure risk and reduced drug investigating time and costs [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…Techniques for small molecule screening such as cell panel screening are widely used for investigating in vitro biological mechanism and drug discovery ( Figure 1 ). A number of groups have investigated the role of various glycogen synthase kinase-3 (GSK3)-inhibiting small molecules in the regeneration and differentiation of odontogenic stem cells, primarily endogenous to tissues of the dental pulp and dentin ( Neves et al, 2017 ; Neves & Sharpe, 2018 ; Birjandi et al, 2020 ; Masuda et al, 2020 ). GSK3 has been identified as a key enzyme in the modulation of many signaling pathways responsible for the growth and maturation of bone, including those common to the formation of craniofacial and dentoalveolar tissues e.g., the Wnt/β-catenin pathway which has been demarcated as a pertinent cascade in stem cell differentiation and the regulation of dentin repair.…”
Section: In Vitro Evidence Of Small Molecules On Craniofacia...mentioning
confidence: 99%
“…GSK3 has been identified as a key enzyme in the modulation of many signaling pathways responsible for the growth and maturation of bone, including those common to the formation of craniofacial and dentoalveolar tissues e.g., the Wnt/β-catenin pathway which has been demarcated as a pertinent cascade in stem cell differentiation and the regulation of dentin repair. One such study has shown that five unique small molecule drugs known to work through different mechanisms of action (Famotidine, Olanzapine, Naproxen, Cromolyn, and Tivantinib) are capable of acting as inhibitory agents against GSK3 ( Birjandi et al, 2020 ). Of these drugs, Tivantinib—a non-ATP competitive small molecule mainly used in the treatment of hepatocellular carcinoma—was observed to incite Axin2 expression and Wnt/β-catenin pathway signaling at a low concentration (50 nM) while simultaneously maintaining dental pulp cell viability through inconsequential levels of toxicity, thus potentially making it a suitable candidate for in vivo studies on the natural regeneration of odontoblasts necessary for reversing profound dentinal lesions and enhancing dentin preservation.…”
Section: In Vitro Evidence Of Small Molecules On Craniofacia...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo application of LiCl in rat molars results in higher β-catenin and a complete tertiary dentin (22). A number of small molecules that inhibit glycogen synthase kinase 3 (GSK3), a key enzyme in Wnt signalling pathway, have been shown to promote activation of Wnt pathway in vitro and dentin repair in mice and rats with experimental pulp exposures (23)(24)(25)(26). Treatment of dental pulp exposures with Semaphorin 3A, promotes formation of an odontoblastic layer, dentin tubules, and predentin (27).…”
Section: Wnt Signalling In Tooth Homeostasismentioning
confidence: 99%